Scientific Knowledge about Poultry Broiler Farming in Barabanki District of Uttar Pradesh (Indian Journal of Extension Education, 2016)
The present investigation was carried out to study the scientific knowledge about broiler farming among poultry farmers in Barabanki district of Uttar Pradesh. The fifteen poultry farmers were selected randomly from each block, making a total sample size of 75. The study revealed that all the small poultry farmers had medium level of scientific knowledge about feed and feeding management practices, housing management practices and brooding management practices (in overwhelming majority), while all the large poultry farmers had high level of scientific knowledge about housing management practices, breed selection and identification of quality chicks, feed and feeding management practices and poultry insurance. All the medium poultry farmers were found to have medium level of scientific knowledge about biosecurity and disease control practices, finance, marketing and poultry insurance, while overwhelming majority of them (93.75%) were having high level of knowledge about feed and feeding management practices. Further, comparison of knowledge level about scientific broiler farming among the different categories of poultry farmers using one way ANOVA was also done and the results show that small, medium and large poultry farmers were found to differ significantly at 1% level of significance (p<0.01) with respect to knowledge about scientific broiler farming practices.